Journal of Engineering and Applied Science - Mourad, Sherif; Huzayyin, Ali .; Ettouney , Reem .; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The Journal of Engineering and Applied Science publishes fundamental and applied research articles and reviews spanning different areas of engineering disciplines, applications, and interdisciplinary topics. These include, but are not limited to, the following areas: Architectural Engineering: architectural studies, building science and technology, environmental design, energy efficiency and renewable energy in buildings and sites, urban design and community development, housing, urban planning and development. Chemical Engineering: chemical process systems engineering, separation operations, reaction kinetics and thermodynamics, and applications to organic, inorganic, and environmental technologies. Civil Engineering: numerical modelling of structures, seismic evaluation, experimental testing, construction and management, geotechnical engineering, water resources management, groundwater modelling, coastal zone modelling, offshore structures, water processes, desalination, waste-water treatment, pavement and maintenance, transport and traffic, laser scanning, and hydrographic surveying. Electrical Engineering: artificial and machine intelligence and robotics, automatic control, bioinformatics and biomedical engineering, communications, computer engineering and networks, systems security and data encryption, electric power engineering and drives, embedded systems, Internet of Things (IoT), microwaves and optics. Engineering Mathematics and Physics: computational and stochastic methods, optimization, nonlinear dynamics, modelling and simulation, computer science, solid state physics and electronics, computational electromagnetics, biophysics, atomic and molecular physics, thermodynamics, geophysical fluid dynamics, wave mechanics, and solid mechanics. Mechanical Engineering: machine design, materials science, mechanics of materials, manufacturing engineering and technology, dynamics, robotics, control, industrial engineering, ergonomics, energy, combustion, heat transfer, fluids mechanics, thermodynamics, turbo machinery, aerospace research, aerodynamics, and propulsion. Mining, Petroleum and Metallurgy: mine/tunnel ventilation, ore dressing, powder technology, rock mechanics, geology and applied mineralogy, oil and gas formations, well drilling, production technologies, reservoir engineering, physical and extractive metallurgy and new and advanced materials. and topics related to sustainable development through engineering including policy formation, development of public understanding of engineering, the use of engineering to respond to global challenges, engineering education and research methods, and engineering as a driver of innovation.
Keywords: Engineering; Civil engineering; Chemical engineering; Technology and Engineering; Civil Engineering; Chemical Engineering